[Ru(salen)(NO)] complex encapsulated in mesoporous SBA-16 as catalyst for hydrogenation of ketones - Bordoloi, Ankur; Amrute, Amol P.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
SBA-16 mesoporous silica with cubic lm3m structure was synthesized using Pluronic F127 poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer (EO106PO70EO106) and it blends with Pluronic P123 triblock copolymer (EO20PO70EO20) as supramolecular templates. The resulting material was used for encapsulating [Ru(salen)(NO)] complex and used in the hydrogenation of ketones to the corresponding alcohols. The pore entrance size of SBA-16 was precisely tailored by silylation with diphenyldichlorosilane to trap [Ru(salen)(NO)] complex in the cage of SBA-16. Small angle XRD, N-2 sorption measurements, UV-Vis and FT-IR analysis evidences the structural integrity of mesoporous silica as well as the complex. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Encapsulation; Hydrogenation; Ketones; SBA-16; [Ru(salen)(NO)] complex

WO3/70% TBHP/aqueous NaOH: an efficient catalytic combination for the selective oxidation of methylarenes and alkyl aryl ketones to benzoic acids - Shaikh, Tanveer Mahammad Ali; Sudalai, Arumugam (European Journal of Organic Chemistry, 2008)
A new solvent-free, reusable catalytic combination consisting Of WO3/70% TBHP/aqueous NaOH has been described for the direct oxidation of methylarenes and acetophenones to the corresponding benzoic acids in high yields. Alkylarenes are oxidized to the corresponding aromatic ketones or benzylic alcohols depending upon whether NaOH is used or not. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: Arenes; Benzoic acids; Ketones; Oxidation; Tungsten

Catalytic asymmetric transfer hydrogenation of ketones using [Ru(p-cymene)Cl-2](2) with chiral amino alcohol ligands - Deshpande, Sudhindra H.; Kelkar, Ashutosh A.; Gonnade, Rajesh G.; Shingote, Savita K.; Chaudhari, Raghunath V. (Catalysis Letters, 2010)
Catalytic asymmetric transfer hydrogenation of aromatic alkyl ketones has been investigated using [Ru(p-cymene)Cl-2](2) and new derivatives of beta-amino alcohols synthesized from (S)-(-)-lactic acid and mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%). Asymmetric transfer hydrogenation of ketones has been investigated using [Ru(p-cymene)Cl-2](2) and beta-amino alcohols synthesized from (S)-(-)-lactic acid and Mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%).
Keywords: Amino alcohol ligand; Asymmetric transfer hydrogenation; Ketones; Ru catalyst

Pd-catalyzed selective hydrosilylation of aryl ketones and aldehydes - Chouthaiwale, Pandurang V.; Rawat, Varun; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Pd salts in combination with triethylsilane as hydride source and DMF as solvent has been found to be excellent catalytic combination that selectively reduces aryl ketones and aldehydes under mild conditions to afford triethylsilyloxy compounds in excellent yields. Product selectivity to the respective benzyl alcohols can however be achieved when the reaction was performed in DMF/H2O (4:1) as solvent system. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Hydrosilylation; Ketones; Palladium; Triethylsilane

Stable silanone with a three-coordinate silicon atom: a century-long wait is over - Sen, Sakya S. (Angewandte Chemie-International Edition, 2014)
Keywords: cations; germanones; Ketones; silanones; transition metals

Modular synthesis of dihydroxyacetone monoalkyl ethers and isosteric 1-hydroxy-2-alkanones - Gueclue, Deniz; Rale, Madhura; Fessner, Wolf-Dieter (European Journal of Organic Chemistry, 2015)
Straightforward methods for the efficient, systematic preparation of libraries of the title compound classes have been evaluated. A general and efficient modular route to dihydroxyacetone monoethers was developed based on trityl glycidol, which, through epoxide opening, oxidation, and deprotection, provided variously alkylated ethers by three routine operations in good overall yields (eight examples, 24-59%). The preparation of structurally related 1-hydroxyalkanones depends on the availability of the most economic starting materials and on their physicochemical properties. Thus, the most practical one-step approaches consisted of the sec-selective oxidation of short-chain 1,2-diols (<= C-6) using NaOCl, and the direct ketohydroxylation of 1-alkenes (>= C-6) using buffered stoichiometric KMnO4 or catalytic RuO4 with reoxidation by oxone, for which mostly good overall yields were achieved on a multigram scale (nine examples, 15-78%).
Keywords: Alkylation; Hydroxylation; Ketones; Oxidation; Oxygenation; Regioselectivity; synthetic methods

Scandium triflate catalyzed unexpected cleavage of C-C bonds in ynones - Kavthe, Rahul D.; Bansode, Avinash H.; Patil, Nitin T. (Arkivoc, 2016)
An unexpected C-C bond cleavage in ynones in the presence of catalytic amounts of Sc(OTf)(3) in methanol under microwave irradiation has been discussed. The effect of substituent on the regioselectivity of C-C bond cleavage has carefully been addressed by employing various ynones derivatives. The mechanism has been proposed for the observed regioselectivity.
Keywords: C-C bond cleavage; Esters; Ketones; scandium triflate; ynones

C(sp(3))-F, C(sp(2))-F and C(sp(3))-H bond activation at silicon(II) centers - Swamy, V. S. V. S. N.; Parvin, Nasrina; Raj, K. Vipin; Sen, Sakya S. (Chemical Communication, 2017)
Silylene [PhC(NtBu)(2)SiN(SiMe3)(2)] (1) cleaves the C(sp(3))-H and C-F bonds of acetophenone and 1,1,1-trifluoroacetophenone, respectively, under mild conditions. The reaction is initiated via a nucleophilic attack from the oxygen to the silicon atom followed by C-F/H bond cleavage. The scope of C-F bond activation has further been extended with C6F6 and C6F5CF3.
Keywords: Boron triple bond; C-F Bond; Fluorinated Building-Block; H Activation; Ketones; N-heterocyclic carbenes; Oxodative Addition; Perfluorinated Arenes; Selective Activation; Transition-Metal Centers

Hemiketal-keto tautomerism in 2-deoxy-delta-lactones mediated by 2-lithiothiazole in solution state: a formal synthesis of DAH, Kamusol and their C-5 Epimers - Chand, Hemender R.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2019)
The reactions of 2-lithiothiazole on 3,4,6-tri-O-benzyl-2-deoxyglyconolactones have been studied, which resulted in the formation of two products, major (3,4,6-tri-O-benzyl-2-deoxy-1-(2-thiazolyl) glycal) and minor products 3,4,6-tri-O-benzyl-2-deoxy-1-(2-thiazolyl) glycal hemiketal. The hemiketal-keto tautomerism in solution was observed in the minor product. The tautomerism has been studied in various organic solvents and their ratios have been determined by H-1 NMR spectroscopy. The major product from the reaction of 2-lithiothiazole with 2-deoxygluconolactone was utilized for the synthesis of 3-deoxy-D-arabino-2-heptulosonic acid DAH 4 a and 3-deoxy-D-arabino-2-heptulopyranose commonly known natural product kamusol 6 a via acid catalyzed hydration followed by stereoselective methyl glycoside bond formation. Similarly, major product from 2-deoxygalactonolactone furnished 5-epi-DAH 4 b (C-5 epimer of 4 a) and 5-epi-kamusol 6 b (C-5 epimer of 6 a). The minor product has also been utilized for the synthesis of DAH 4 a, 5-epi-DAH 4 b, kamusol 6 a and 5-epi-kamusol 6 b through a common intermediate, alpha-methyl glycosylated product.
Keywords: hemiketals; Ketones; tautomerism; thiazoles; umpolung